Synthesis and characterization of poly(3-thiophenyl acetic acid) (P3TAA)-BaFe12O19 nanocomposite - Durmus, ZEHRA; Unal, B.; Toprak, M. S.; SOZERI, H.; Baykal, A. (My University, 2011)
We have presented a method for the fabrication of poly(3-thiophenyl acetic acid) (P3TAA)-BaFe12O19 nanocomposites by the in situ polymerization of P3TAA in the presence of synthesized BaFe12O19 nanoparticles. The nanoparticles and the nanocomposite were analyzed by XRD, FTIR, TGA, TEM, VSM and conductivity techniques for structural and physicochemical characteristics. Crystallographic analysis revealed the phase as hexaferrite and X-ray line profile fitting yielded a crystallite size of 32 nm. The particles, observed by TEM, exhibit irregular shapes and sizes between 100 and 500 nm, revealing polycrystalline character when compared with the crystallite size from XRD. FTIR and TGA analysis results show that P3TAA is conjugated to the particle surface via a carboxylate group and that the composite has a polymer content of similar to 10%. Magnetic hysteresis curves do not saturate at high fields, which is a characteristic feature of fine particle systems with grain sizes smaller than 1 mu m. Conductivity measurements showed a semiconductor character of the nanocomposite. (C) 2011 Elsevier Ltd. All rights reserved.